2016
DOI: 10.1242/dev.131037
|View full text |Cite
|
Sign up to set email alerts
|

Fat4-Dchs1 signalling controls cell proliferation in developing vertebrae

Abstract: The protocadherins Fat4 and Dchs1 act as a receptor-ligand pair to regulate many developmental processes in mice and humans, including development of the vertebrae. Based on conservation of function between Drosophila and mammals, Fat4-Dchs1 signalling has been proposed to regulate planar cell polarity (PCP) and activity of the Hippo effectors Yap and Taz, which regulate cell proliferation, survival and differentiation. There is strong evidence for Fat regulation of PCP in mammals but the link with the Hippo p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 55 publications
1
19
0
Order By: Relevance
“…Mutations in Fat’s closest mammalian homolog Fat4 (FatJ) and its Ds-like ligands strongly disrupt PCP-like processes, and have in humans been associated with the multisystem defects of Hennekam and Van Maldergem syndromes ( Alders et al, 2014 ; Mao et al, 2011 ; Saburi et al, 2008 ; Zakaria et al, 2014 ). There has been some debate, however, about whether the mammalian proteins retain direct regulation of Hippo activity ( Bagherie-Lachidan et al, 2015 ; Bossuyt et al, 2014 ; Pan et al, 2013 ; Sadeqzadeh et al, 2014 ; Kuta et al, 2016 ). Nonetheless, Fat4 has been linked to Hippo changes in both normal development and tumors ( Qi et al, 2009 ; Van Hateren et al, 2011 ), mutations in Fat4 or Dachsous1 change the balance of precursors and mature neurons in the developing neuroepithelium of both humans and mice, and the mouse defect can be reversed by knockdown of the Yki homolog Yap ( Cappello et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in Fat’s closest mammalian homolog Fat4 (FatJ) and its Ds-like ligands strongly disrupt PCP-like processes, and have in humans been associated with the multisystem defects of Hennekam and Van Maldergem syndromes ( Alders et al, 2014 ; Mao et al, 2011 ; Saburi et al, 2008 ; Zakaria et al, 2014 ). There has been some debate, however, about whether the mammalian proteins retain direct regulation of Hippo activity ( Bagherie-Lachidan et al, 2015 ; Bossuyt et al, 2014 ; Pan et al, 2013 ; Sadeqzadeh et al, 2014 ; Kuta et al, 2016 ). Nonetheless, Fat4 has been linked to Hippo changes in both normal development and tumors ( Qi et al, 2009 ; Van Hateren et al, 2011 ), mutations in Fat4 or Dachsous1 change the balance of precursors and mature neurons in the developing neuroepithelium of both humans and mice, and the mouse defect can be reversed by knockdown of the Yki homolog Yap ( Cappello et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The increased proliferation within the osteogenic progenitors is analogous to the role of Dchs1-Fat4 signalling in the cerebral cortex and heart (Cappello et al, 2013;Ragni et al, 2017) and in contrast to the decreased proliferation observed in the kidney and somites (Kuta et al, 2016;Mao et al, 2011). As in the heart and brain, loss of Dchs1-Fat4 signalling also resulted in increased Yap activity.…”
Section: Discussionmentioning
confidence: 70%
“…Dachsous cadherin-related 1 (DCHS1) expression is up regulated in hypoxic conditions by fivefold and is a cellular adhesion molecule member of the cadherin superfamily. Lack of DCHS1 results in developmental defects of the early sclerotome associated with fewer chondrogenic cells within the developing vertebral body [ 35 ]. Keratin 19 (KRT19) expression showed a fourfold increase in hypoxic cultured samples and is an intermediate filament protein that is part of the keratin family.…”
Section: Resultsmentioning
confidence: 99%